Education and Science: current trends - Chaika L. N., Danilchenko S. L., Dubrovskaia S. A., Zaykovskiy V. E., Illarionov V. A., Illarionov V. A., Zakharova A. N., Dulina G. S., Zhemchuzhnikov D. G., Kuvshinova E. N., Azizova L. K., Rensh M. A., Baryshnikova E. L., Badashkeev M. V., Farberova O. E., Tonkikh V. A., Anisimov V. P., Vasilev P. V., Cherenkov V. G., Kruglov V. N. (Education and Science: current trends, 2016)
in modern scientific literature there are different views about the nature of Russian civilization, the definition of the specific features of Russia as a civilization of the body, about the appropriateness of considering the factor of multi-ethnicity in the study of Russian civilization. The main point of view to the affiliation of our country to one civilization or another
Keywords: российская цивилизация; определение специфических черт России; концепции локальных цивилизаций; Russian civilization; definition of specific features of Russia; the legitimacy of considering the factor of multi-ethnicity in the study of Russian civilization; the concept of local civilizations; stability of major civilizational features of Russia; правомерность учета фактора многонациональности; изучение российской цивилизации; устойчивость основных особенностей; цивилизационные особенности России